1999
DOI: 10.1093/ajcn/70.3.405
|View full text |Cite
|
Sign up to set email alerts
|

Aging, body composition, and lifestyle: the Fels Longitudinal Study

Abstract: Background: Changes in body composition in men and women occur with age, but these changes are affected by numerous covariate factors. Objective: The study examined patterns of change in body composition and determined the effects of long-term patterns of change in physical activity in older men and women and in menopausal status and estrogen use in women. Design: Serial measures of height, weight, body mass index (BMI), total body fat (BF), percentage BF, and fat-free mass (FFM) from underwater weighing of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
195
7
24

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(246 citation statements)
references
References 22 publications
20
195
7
24
Order By: Relevance
“…These changes are more dramatic than those in our 9 established and stable RA control patients (i.e., annual changes of Ϫ0.68% in ALM and ϩ2.9% in FM), and this is consistent with our finding that muscle loss primarily occurs early in disease, probably prior to treatment (14). The annual rate of loss of LM we observed for our followup control patients (0.10 kg) is similar to that reported for age-matched individuals from the general population (men: 0.07 kg/year, women receiving estrogen: 0.08 kg/ year, women not receiving estrogen: 0.16 kg/year), but the rate of FM gain is higher (0.81 kg/year versus 0.37 kg/year and 0.41 kg/year for men and women, respectively) (15). These findings, albeit on a small sample, together with our earlier results (14), suggest that the rate of muscle loss in RA patients is increased during the initial phase of disease 74 Lemmey et al and, provided disease is controlled, then is reduced to rates normal for sedentary individuals, while the rate of FM accumulation may be chronically elevated.…”
Section: Discussionsupporting
confidence: 82%
“…These changes are more dramatic than those in our 9 established and stable RA control patients (i.e., annual changes of Ϫ0.68% in ALM and ϩ2.9% in FM), and this is consistent with our finding that muscle loss primarily occurs early in disease, probably prior to treatment (14). The annual rate of loss of LM we observed for our followup control patients (0.10 kg) is similar to that reported for age-matched individuals from the general population (men: 0.07 kg/year, women receiving estrogen: 0.08 kg/ year, women not receiving estrogen: 0.16 kg/year), but the rate of FM gain is higher (0.81 kg/year versus 0.37 kg/year and 0.41 kg/year for men and women, respectively) (15). These findings, albeit on a small sample, together with our earlier results (14), suggest that the rate of muscle loss in RA patients is increased during the initial phase of disease 74 Lemmey et al and, provided disease is controlled, then is reduced to rates normal for sedentary individuals, while the rate of FM accumulation may be chronically elevated.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, our data con®rms previous reports (Baumgartner et al, 1995) that fat mass, in terms of percentage fat mass, may be relatively stable in elderly men but may decrease with age in elderly women. Fat mass gain was lower in our subjects`60 y (0.21 kgay in men and 0.14 kgay in women) compared to 0.37 kgay and 0.41 kgay reported by Guo et al (1999) in men and women, respectively, and may be explained by lower rates of weight gain with age in our subjects, Percentage fat mass was lower in our subjects than in subjects with higher weights reported by Cohn et al, (1985). We found trunk and appendicular fat mass became progressively higher until 60 ± 74 y, where peak fat mass was noted in men and women and was lower thereafter.…”
Section: Fat Masscontrasting
confidence: 59%
“…A number of studies (Bartlett et al, 1991;Deurenberg et al, 1991;Gallagher et al, 1995Gallagher et al, , 1996Guo et al, 1999) have evaluated associations between body composition parameters and age in healthy subjects. Nevertheless this is the ®rst study to evaluate lean body parameters (FFM, ASMM, BCM, TBK) and fat mass, derived from two independent methods, in 433 healthy subjects between 18 and 94 y and compared their differences between age groups and between genders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lean body mass and skeletal muscle mass decrease and fat mass increases (Ho et al 2010;Sowers et al 2007;Sternfeld et al 2004). As the time after the menopause increases, the increases in fat mass and body weight become greater (Guo et al 1999). It has been shown that maintaining or increasing participation in regular physical activity contributes to the prevention or the attenuation of those gains (Sternfeld et al 2004).…”
Section: Discussionmentioning
confidence: 99%